2017
DOI: 10.1002/cssc.201700852
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Dendritic Pt Nanostructure with High‐Index Facets as Highly Active and Durable Electrocatalyst for Oxygen Reduction

Abstract: The durability issues of Pt catalyst should be resolved for the commercialization of proton exchange membrane fuel cells. Nanocrystal structures with high-index facets have been recently explored to solve the critical durability problem of fuel cell catalysts as Pt catalysts with high-index facets can preserve the ordered surfaces without change of the original structures. However, it is very difficult to develop effective and practical synthetic methods for Pt-based nanostructures with high-index facets. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 88 publications
0
31
0
Order By: Relevance
“…[11][12][13][14][15][16][17] Besides, shape-controlled synthesis of PtÀ M alloy nanocrystals exposing specific facets can further elevate the ORR activity. [18][19][20][21] Extended Pt 3 Ni(111) single crystal surface has been reported to have the highest ORR activity, whose specific activity is 90-fold more active than the state-of-the-art Pt/C catalyst. [22] As a consequence, octahedral or icosahedral Pt 3 Ni nanocrystals bounded by (111) facets are widely explored to gain super high ORR activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] Besides, shape-controlled synthesis of PtÀ M alloy nanocrystals exposing specific facets can further elevate the ORR activity. [18][19][20][21] Extended Pt 3 Ni(111) single crystal surface has been reported to have the highest ORR activity, whose specific activity is 90-fold more active than the state-of-the-art Pt/C catalyst. [22] As a consequence, octahedral or icosahedral Pt 3 Ni nanocrystals bounded by (111) facets are widely explored to gain super high ORR activity.…”
Section: Introductionmentioning
confidence: 99%
“…bimetallic catalysts is an efficient approach to reduce the Pt usage by increasing the electrocatalytic activity [11–17] . Besides, shape‐controlled synthesis of Pt−M alloy nanocrystals exposing specific facets can further elevate the ORR activity [18–21] . Extended Pt 3 Ni(111) single crystal surface has been reported to have the highest ORR activity, whose specific activity is 90‐fold more active than the state‐of‐the‐art Pt/C catalyst [22] .…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the onset and peak potentials (0.45 and 0.57 V RHE , respectively) for the CO oxidation of Pt 1 Ru 1 /C were much lower than those (0.57 and 0.66 V RHE , respectively) of Pt 1 Ru 3 /C, indicating higher CO oxidation activity than Pt 1 Ru 3 /C [26]. However, it was clearly confirmed that the two PtRu/C catalysts still exhibit much higher CO oxidation activities due to the presence of surface Ru atoms compared to a bare Pt/C catalyst [27]. This result corresponded to that of previous reports showing that the change in the CO binding energy depends on the Ru content in PtRu alloys [13].…”
Section: Resultsmentioning
confidence: 99%
“…Design novel cathode materials are also of great significance for improving the performance of LIBs. Molecular electrode materials have been widely used as a substitute for traditional transition metal oxides due to their low price, flexible and environmental friendliness . Finding excellent molecular electrode materials is still very challenging, as the organic structure space is very broad.…”
Section: Machine Learning Application In Energy Materialsmentioning
confidence: 99%
“…Besides the various combinations of bimetallic elements, the mixing ratio is also an influencing factor and Ulissi et al 54 screened all cases of bimetallic Ni x Ga y surfaces for CO 2 RR. Since there are multiple surface facets in the corresponding bulk composition, and adsorption sites on the same surface, it is hard to exhaustively filter all adsorptions configurations on the Ni x Ga y surface, thus the application of NN model can greatly simplify this workflow which is shown in Figure 2a and predict three most active surfaces NiGa(210), NiGa (110), and Ni 5 Ga 3 (021) for CO 2 RR of C1 and C2 products through only several thousand DFT calculation steps. For specific crystal surfaces, their catalytic activities are generally determined by adsorption.…”
Section: Adsorption Energymentioning
confidence: 99%